L’industrie de l’assurance-vie continue sa transformation - Millette, Yves (Assurances)

(untitled) (HEC Montréal, 1988)
In his article written on December 31, 1987, Mr. Yves Millette presents the highlights of life insurance in Canada in 1987. In particular, he points out the significant increase in the types of life annuities available. He also notes that, during the past year, universal life insurance was the most predominant form of life insurance underwritten and that health and accident insurance premiums increased by 13.6%, while benefits rose by 7.8%. In addition, in 1987 personal life insurance companies took advantage of deregulation to acquire, in particular, various financial institutions.